KOMŞU ORGANLARA DOĞRUDAN YAYILMA GÖSTEREN MİDE KARSİNOMU OLGULARINDA REZEKTİF CERRAHİ GİRİŞİMİN SONUÇLARI - ERSAN, Yılmaz; ÇİÇEK, Yusuf; ERTÜRK, Süphan; ERTEM, Metin; ŞAHİN, Dursun Ali (Cerrahpaşa Medical Journal, 2014)
Background and Design. 274 patients with gastric carcinoma had undergone resection between 1989 and 1993. Of 274 patients, 87 (34%) had cancer extending to adjacent organs. In this study, the late results of resective procedures in 87 patients with gastric carcinoma extending to adjacent organs is reported. These 87 patients were classified into two groups: Group I included 38 patients without peritoneal dissemination, liver metastasis and widespread nodal involvement. Group II consisted of 49 patients with positive evidence of incurability. Results. Among group I patients, gastrectomy, complete removal of invaded organs and sufficient lymphadenectomy were performed in 74 patients. In these patients, 5 year survival rate was 31.7%. Remaining 14 patients were treated with gastrectomy alone or with incomplete removal of invaded organs. In these patients, 5year survival rate was 4.1 % and significantly lower than that of 24 patients. In group II there were 49 patients with incurable factors and 5year survival rates were 3.4 and 0% in complete (16) and incomplete (33) excisions, respectively. Conclusion. Gastrectomy, complete removal of invaded organs and sufficient lymphadenectomy should be performed in patients with gastric carcinoma extending to adjacent organs and without positive evidences of incurability. This aggressive surgical treatment (en blac resection) provides higher 5year survival rates than those of incomplete resection. Involvement of one adjacent organ, treated with complete excision, was a sign of a better outcome compared to involvement of multiple adjacent organs.